Operando X-ray absorption investigations into the role of Fe in the electrochemical stability and oxygen evolution activity of Ni1−xFexOy nanoparticles. Issue 47 (22nd November 2018) - Abbott, Daniel F.; Fabbri, Emiliana; Borlaf, Mario; Bozza, Francesco; Schäublin, Robin; Nachtegaal, Maarten; Graule, Thomas; Schmidt, Thomas J.
Abstract : The structural and electronic properties of rock salt-type Ni–Fe oxides are investigated under OER conditions. The inclusion of Fe in the rock-salt structure is shown to inhibit the transformation to more layered and disordered polymorphs. Abstract : Mixed Ni–Fe metal oxides currently represent some of the most attractive anode catalysts for the electrochemical splitting of water in alkaline electrolyte due to their low overpotentials for the oxygen evolution reaction (OER). Here we employ a practical and scalable liquid-feed flame-spray synthesis capable of producing highly crystalline Ni–Fe oxide (Ni1− x Fe x O y ) nanoparticles with high specific surface areas (SABET ≈ 20–75 m 2 g −1 ). The work presented herein focuses on expanding the current understanding of how Fe incorporation influences the surface electronic and local coordination structures of Ni1− x Fe x O y and how this impacts the electrochemical stability and OER activity. The resulting operando XANES and EXAFS analyses at the Ni and Fe K-edges permit useful insight into the nature of the valence states and the rearrangements in local structure that occur under operating conditions representative of alkaline water electrolysis. Specifically, we show that the incorporation of Fe greatly stabilizes the Ni electronic and local coordination environment under OER conditions. Combined with electrochemical measurements, we find that the incorporation of Fe leads to an overall stabilization of the initially compact and crystalline rock salt structure of Ni1− x Fe x O y and thereby inhibits the transformation to more layered and disordered polymorphs ( e.g. β/γ-Ni1− x Fe x OOH).